Prevalence of non-alcoholic fatty liver disease and advanced fibrosis in Hong Kong Chinese: a population study using proton-magnetic resonance spectroscopy and transient elastography - Wong, Vincent Wai-Sun; Chu, Winnie Chiu-Wing; Wong, Grace Lai-Hung; Chan, Ruth Suk-Mei; Chim, Angel Mei-Ling; Ong, Arlinking; Yeung, David Ka-Wai; Yiu, Karen Kar-Lum; Chu, Shirley Ho-Ting; Woo, Jean; Chan, Francis Ka-Leung; Chan, Henry Lik-Yuen (Gut, 2012)
ObjectiveKnowledge of the epidemiology of non-alcoholic fatty liver disease (NAFLD) is incomplete because liver biopsy cannot be performed on the general population to assess disease severity. New non-invasive tests allow accurate and safe assessment in healthy individuals. The aim of this study was to examine the prevalence of NAFLD and advanced fibrosis in the general Hong Kong Chinese population.MethodsSubjects were recruited from the community by random selection from the government census database. Liver fat and fibrosis were assessed by proton-magnetic resonance spectroscopy and transient elastography, respectively.ResultsOverall, 264 of 922 (28.6%) subjects had intrahepatic triglyceride content ≥5%. Excluding 12 subjects with significant alcohol consumption, the population prevalence of NAFLD was 27.3% (95% CI 24.5% to 30.2%). Each component of the metabolic syndrome increased the risk of fatty liver in a dose-dependent manner (prevalence of 4.5% in subjects without any component and 80.0% in those with all five components). 8 (3.7%) patients with fatty liver had liver stiffness ≥9.6 kPa, a level suggestive of advanced fibrosis. Body mass index and alanine aminotransferase level were independent factors associated with liver stiffness. Together with other clinical prediction scores, the estimated prevalence of advanced fibrosis in patients with fatty liver in the community was <10%. Compared with non-drinkers, modest drinkers (<10 g per day) did not have higher risk of fatty liver after adjustment for demographic and metabolic factors. The liver stiffness was 4.7±1.9 kPa in modest drinkers and 4.6±1.7 kPa in non-drinkers (p=0.54).ConclusionNAFLD is found in over a quarter of the general adult Chinese population, but the proportion of patients with advanced fibrosis is low. Modest alcohol consumption does not increase the risk of fatty liver or liver fibrosis.